To determine the sequence of transformations that maps ΔA(-5,2)B(-2,4)C(-3,0) to ΔA''(-1,-2)B''(2,-4)C''(1,0), we need to analyze the transformation.
-
Start with the coordinates of the points in ΔA and ΔA'':
- A(-5, 2) → A''(-1, -2)
- B(-2, 4) → B''(2, -4)
- C(-3, 0) → C''(1, 0)
-
First, let's identify the transformations. We need to look for a transformation that first reflects the points over the x-axis and then translates the points.
-
Reflection over the x-axis:
- Reflecting points over the x-axis changes the sign of the y-coordinate.
- For A: (-5, 2) → (-5, -2)
- For B: (-2, 4) → (-2, -4)
- For C: (-3, 0) → (-3, 0)
After this reflection, we have:
- A'(-5, -2)
- B'(-2, -4)
- C'(-3, 0)
-
Translation:
- Now we need to translate these reflected points to their final coordinates: A''(-1, -2), B''(2, -4), C''(1, 0).
- From A'(-5, -2) to A''(-1, -2), we translate right by 4 (increase x by 4).
- From B'(-2, -4) to B''(2, -4), we also translate right by 4.
- From C'(-3, 0) to C''(1, 0), we translate right by 4.
Combining these transformations gives us:
- Reflect over the x-axis: \( (x, y) → (x, -y) \)
- Translate right by 4: \( (x, y) → (x + 4, y) \)
The entire transformation can be represented as:
- Reflect over x-axis: \( (x, y) → (x, -y) \)
- Then translate: \( (x, -y) → (x + 4, -y) \)
So the composition of transformations can be summarized as: \( (x, y) → (x + 4, -y) \)
Now let’s look at the provided options:
- \( (x,y) → (x + 4, -y) \)
This matches exactly with the transformation we deduced.
Thus, the correct answer is: \( \text{(x,y)→(x+4,-y)} \)